Democracy and participation at the local level in the context of city (citizens') council: Women's and children's assemblies in Zeyti̇nburnu, Küçükçekmece, Kadıköy and Bahçeli̇evler - Vanlıoğlu, Esma (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü / Uluslararası İlişkiler Anabilim Dalı, 2015)
Bu tez, yerel düzeyde demokrasi ve katılım olgusunu kent konseyi modeli bağlamında İstanbul dahilinde Zeytinburnu, Küçükçekmece, Kadıköy ve Bahçelievler ilçeleri Kent Konseyleri kadın ve çocuk meclisleri örneklemleri üzerinden incelemektedir. Türkiye bağlamında kent konseyi kadın ve çocuk meclislerinin yerel düzeyde demokrasi ve katılımı sağlama konusunda rolü araştırılmıştır. Araştırmada, kent konseyleri kadın ve çocuk meclisleri, yerel düzeyde kadın ve çocuk katılımı bağlamında incelenmektedir. Bu tez dahilinde, yerel düzeyde demokrasi ve katılımı gerçekleştirmek amacıyla yönetişim yaklaşımı doğrultusunda Birleşmiş Milletler Kalkınma Programı (BMKP) tarafından sunulan Yerel Gündem 21 (YG21) projesi kapsamında bir katılım modeli olarak oluşturulan kent konseylerinin uygulanması aşamasında karşılaşılan sorunlar irdelenmiştir. Araştırma sonuçları, kent konseyi kadın ve çocuk meclislerinin yerel düzeyde demokrasi ve katılımı sağlama konusunda aktif olarak çalışmalarına rağmen beklenen doğrultuda kadın ve çocuk katılımını gerçekleştiremediğini göstermiştir. Kent konseyi modeli ile kadın ve çocuk meclisleri, uygulama sürecinde karşılaşılan sorunlar çözüldüğünde demokrasi ve siyasi anlamda karar verme süreçlerine katılım konularında daha etkin düzeyde katkı sağlayacaklardır.
Kent konseyi bağlamında yerel düzeyde demokrasi ve katılım: Zeytinburnu, Küçükçekmece, Kadıköy ve Bahçelievler kadın ve çocuk meclisleri
This thesis deals with the democracy and participation concepts in the context of city (citizens') council model at the local level by sampling Zeytinburnu, Küçükçekmece, Kadıköy and Bahçelievler City Councils women's and children's assemblies in Turkey. The research explores the role of city council women's and children's assemblies in democracy and participation at the local level in the Turkish context. The research explores city (citizens') council women's and children's assemblies in terms of women's and children's participation. This thesis specifically questions the problems of city (citizens') council participation model which starts with Local Agenda 21 (LA21) project by United Nations Development Programme (UNDP) in the context of governance approach in order to realize democracy and participation at the local level. The research has revealed that city (citizens') council women's and children's assemblies could not achieve women's and children's participation in an expected manner although remarkable active works of assemblies to ensure democracy and participation at the local level. In this thesis, it has been stated that city (citizens') council model with women's and children's assemblies will contribute to democracy and participation in political decision-making processes more effectively if the problems encountered in the implementation process are resolved.
Keywords: Demokrasi; Democracy; Demokratik Tutum; Democratic Attitude; Halk Katılımı; Public Participation; Kadınlar; Women; Kararlara Katılma; Decision Making Participation; Kent Konseyleri; City Councils; Yerel Demokrasi; Local Democracy; Yerel Meclisler; Local Assemblies; Children; Çocuklar